Walk in my combat boots : true stories from America's bravest warriors - Patterson, James, 1947-; Eversmann, Matt; Mooney, Chris (Little, Brown and Company, 2021)
Shares firsthand wartime accounts describing the courageous battlefield sacrifices of men and women from every branch and operational specialty of the U.S. military, from the Vietnam War through the present.